Human Security In The Protection of Indonesian Migrant Workers: A Case Study of Trafficking In Persons 'Online Scams' In The Philippines - Ramanitya C Khadifa (Dinasti International Journal of Education Management And Social Science, 2024)
The issue of job fraud victims through online recruitment or online scams has become widespread in the Southeast Asia region. The high flow of mobilization between countries and the ease of visa-free facilities increase the risk of human security threats, including the crime of trafficking in persons (TIP). This paper aims to explain Indonesia’s efforts to protect Indonesian citizens/Indonesian Migrant Workers (PMI) victims of TIP, particularly in the Philippines. The concept of personal security helps identify new security threats that directly impact individuals or citizens. Considering the ease of mobilization and technology, it is possible that future cases caused by online scams will increase. This paper aims to highlight issues that have been overlooked in current discussions. The study adopts a qualitative- descriptive methods, including desk and library research data collection techniques, as well as direct observation. The analysis reveals that successful efforts to protect Indonesian migrant workers in the Philippines contribute to the realization of a key human security concept: freedom from fear. However, there has been no cooperation between Indonesia and the Philippines to prevent similar cases from occurring in the future.